Longitudinal changes in science identity, research self-efficacy, and academic self-concept for biomedical research trainees at a Hispanic-serving institution - Reyes, Clarissa; Wagler, Amy; Monarrez, Angelica (Frontiers in Education, 2025)
IntroductionThis manuscript explores the development of key academic indicators among underrepresented minority students engaged in biomedical research training. Focusing on research trainees at a minority-majority Hispanic-Serving Institution (HSI), the study examines the structural changes and co-variation in student reported measures of science identity, research self-efficacy, and academic self-concept over two time points, spanning the begining and conclusion of research training in biomedical sciences.MethodsUsing Exploratory Graph Analysis (EGA) models, the analysis obtained from biomedical research trainees models changes in the associations between these indicators. The study also investigates how network structure varies by gender and ethnicity, in order to examine any differences in the experiences of male, female, Hispanic, and non-Hispanic students undergoing biomedical research training at an HSI.ResultsThe analysis reveals important differences in the experiences of male, female, Hispanic, and non-Hispanic students undergoing research training at an HSI. The findings underscore the importance of these constructs in shaping student success, particularly noting the positive relationship between research self-efficacy and science identity.DiscussionThe findings offer insights for fostering minority student retention and success in STEMM fields by highlighting the role of science identity and research self-efficacy.